2000
DOI: 10.1063/1.126704
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation mechanism for hydrogen-implanted Si1−xGex/Si(100) heterostructures

Abstract: A mechanism of strain relief of H+ ion implanted and annealed pseudomorphic Si1−xGex/Si(100) heterostructures grown by molecular beam epitaxy is proposed and analyzed. Complete strain relaxation was obtained at temperatures as low as 800 °C and the samples appeared free of threading dislocations within the SiGe layer to the limit of transmission electron microscopy analysis. In our model, H filled nanocracks are assumed to generate dislocation loops, which glide to the interface where they form strain relievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
67
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 12 publications
(14 reference statements)
5
67
0
Order By: Relevance
“…The motion of the two TDs in opposite directions results in an extension of the MD segment leading to strain relaxation of the SiGe layer. 7 The generation of dislocation loops by overpressurized He platelets has been observed in Si ͑Ref. 7͒ as well as in SiC ͑Ref.…”
mentioning
confidence: 99%
“…The motion of the two TDs in opposite directions results in an extension of the MD segment leading to strain relaxation of the SiGe layer. 7 The generation of dislocation loops by overpressurized He platelets has been observed in Si ͑Ref. 7͒ as well as in SiC ͑Ref.…”
mentioning
confidence: 99%
“…We have recently shown that this can be efficiently achieved by He + ion implantation and subsequent thermal annealing. 5,6 In a model of this process, 6 we have assumed that the narrow defect band formed upon ion implantation underneath the SiGe/ Si-substrate interface provides a high density of dislocation loops during annealing, part of which glides to the interface and evolves from there into dislocation arms consisting of segments of misfit dislocations ͑MDs͒ in the interface and threading dislocations ͑TDs͒ through the strained SiGe layer. The stress driven propagation of the TD segments through the SiGe layer along the ͓110͔ and ͓−110͔ directions is associated with an extension of the corresponding MD segments involving an increasing strain relaxation.…”
mentioning
confidence: 99%
“…As shown previously, He-filled cavities, underneath the SiGe layer are responsible for the formation of dislocation loops which glide towards the interface. 4 Under compressive plane stress in SiGe, one segment of such a loop is held at the interface where it forms a MD segment while the other one is driven through the SiGe layer towards the SiGe/ Si top interface.…”
Section: ͑1͒mentioning
confidence: 99%
“…It provides a high density of dislocation loops as sources for misfit dislocations (MDs) yielding efficient strain relaxation during annealing with low densities of threading dislocations (TDs). 3,4 For the strain transfer we make use of the propagation of the dislocations from the bottom of the relaxing SiGe layer towards the surface into the Si cap. This process differs from purely thermally induced strain relaxation where low densities of dislocations are nucleated randomly at the surface.…”
mentioning
confidence: 99%